Management of bacterial neonatal diarrhea in calves (International Seven Journal of Multidisciplinary, 2024)
Diseases such as neonatal diarrhea are common in poorly managed herds and can cause major losses in any cattle breeding system in the world, especially in intensive systems, accounting for 2% of herd losses. As soon as the calf is born, it is exposed to numerous factors, such as agents, the host and the environment, which together can favor the onset of this disease because, due to the reproductive characteristics of the female bovine, there is no transfer of transplacental immunity to the newborn.